Beneficial Effects of Olive Oil Enriched with Lycopene on the Plasma Antioxidant and Anti-Inflammatory Profile of Hypercholesterolemic Patients - Jesus Roman Martínez Álvarez; Ana Belen Lopez Jaen; Monica Cavia-Saiz; Pilar Muñiz; Victoria Valls-Belles (MDPI AG, 2023)
Olive oil and lycopene are foods that have potent antioxidant activity. The objective was to determine the effects of consumption of olive oil enriched with lycopene on oxidative stress biomarkers in hypercholesterolemic subjects. We examined the effects of oil enriched with lycopene extract daily intake during 1 month on plasma antioxidant capacity, lipids profile (triacylgycerols, total cholesterol, cHDL; cLDL, ox-LDL), biomarkers of oxidative stress, and inflammatory markers related with atherosclerosis risk (C-reactive protein (CRP), IL-6; sDC4L) in subjects hypercholesteremics (cholesterol > 220 mg/dL). In the group consuming olive oil-lycopene, significant increases (p < 0.05) in the levels of plasma lycopene concentration (0.146 ± 0.03 versus 0.202 ± 0.04 (µmol/L)), α-carotene (0.166 ± 0.064 versus 0.238 ± 0.07) and in β-carotene (0.493 ± 0.187 versus 0.713 ± 0.221) were observed. These results are linked with the increases of plasma antioxidants and decreases biomarkers of oxidative stress (carbonyl groups, malondialdehyde and 8-hydroxy-deoxiguanosine) observed in hypercholesterolemic group. In relation to lipid profile, a significant decrease was observed in the levels of ox-LDL (781 ± 302 versus 494 ± 200), remaining unchanged the levels of TG, cholesterol, HDL and LDL-c. Regarding inflammatory biomarkers, the levels of CRP and IL-6 decreased significantly. The positive results obtained in this study support the use of olive oil enriched with lycopene to reduce the risk of coronary disease.